Peningkatan Mutu Pendidikan SMA Muhammadiyah 2 Sidoarjo sebagai Sekolah Berkategori The Outstanding School of Muhammadiyah - Hidayatulloh Hidayatulloh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article examines about improving the education quality of SMA Muhammadiyah 2 Sidoarjo as the Outstanding School of Muhammadiyah. This article reveals that the quality improvement of SMA Muhammadiyah 2 Sidoarjo was conducted through: the arrangement of school program and self evaluation, the reinforcement of vision, mission and education objective, the reinforcement of leadership and teamwork, the improvement of teachers and educators competence, the improvement learners quality input, the development of curriculum and learning, the development of school culture, the development of facilities and infrastructure, the development of community service, the cooperation of education and student exchange, the mobilization of education funding resources, the develop-ment of SIM, monitoring and evaluation, and education quality system. The management quality of SMA Muhammadiyah 2 Sidoarjo was run through input-process-output formula. The process of quality containes the process of quality planning, main process, supporting process, dan quality improvement process. Factors supporting the quality improvement are: Muhammadiyah’s popular name, the doctrine of education quality improvement, the leadership of TORSIE paradigm, the school academicians’ spirit of gaining achievement, the synergy of school academicians, the appropriate facilities, and the supports of all stakeholders.